Exercise versus vasodilator stress limb perfusion imaging for the assessment of peripheral artery disease - Davidson, Brian P.; Belcik, J. Todd; Landry, Gregory; Linden, Joel; Lindner, Jonathan R. (Echocardiography (Mount Kisco, N.Y.), 2017)
Purpose Our aim was to determine whether pharmacologic vasodilation is an alternative to exercise stress during limb perfusion imaging for peripheral artery disease (PAD). Methods Quantitative contrast‐enhanced ultrasound (CEU) perfusion imaging of the bilateral anterior thigh and calf was performed in nine control subjects and nine patients with moderate to severe PAD at rest and during vasodilator stress with dipyridamole. For those who were able, CEU of the calf was then performed during modest plantar flexion exercise (20 watts). CEU time‐intensity data were analyzed to quantify microvascular blood flow (MBF) and its parametric components of microvascular blood volume and flux rate. Results Thigh and calf skeletal muscle MBF at rest was similar between control and PAD patients. During dipyridamole, MBF increased minimally (<twofold) for all groups and there were only nonsignificant trends for a reduction in calf MBF in those with PAD (13.5±6.9, 10.0±4.7, and 8.2±6.1 IU/s, for controls, moderate, and severe PAD, respectively; P=.11). In contrast, MBF during modest planar flexion exercise increased markedly in controls but not PAD patients (87.9±79.9 vs 15.2±12.9 IU/s, P<.05). In three moderate PAD patients restudied after undergoing surgical revascularization, MBF during dipyridamole did not change, whereas exercise MBF increased by an average of sevenfold. Conclusions Resting limb skeletal muscle MBF in patients with moderate to severe PAD is similar to that in normal subjects. However, differences in hyperemic flow during contractile exercise but not during dipyridamole allow evaluation of the degree of flow impairment from PAD and the degree of improvement with revascularization.